Pengaruh Kualitas Pelayanan dan Kepuasan Konsumen Terhadap Minat Beli Ulang Pada Toko Grosir Zahra Purwasari Kabupaten Karawang - Mohammad Ferda Aji Perdana; Dedi Mulyadi (Yayasan Daarul Huda Kruengmane, 2023)
Progress in the economic field so far has brought many rapid developments in the business sector. In line with that, many wholesale organizations have sprung up, ranging from the real to the virtual (virtual) world. There are several types of Wholesale organizations namely: Wholesalers, self-service, specialty stores, department stores, supermarkets, convenience stores, and discount, self-selected, limited service and full service retailers. The increasing number of shopping places in big cities as well as in small towns creates a lot of competition. The managers of shopping places in Purwasari, Karawang Regency, one of which is the Zahra Wholesale Store, also want to get a high market share. The way to win the competition is to provide customer satisfaction, starting with providing shopping facilities such as comfortable shopping places, spacious parking lots, spacious shopping areas, besides seating. The purpose of the study was to examine service quality, consumer satisfaction and repurchase interest at the Zahra Wholesale Store, as well as to examine the effect of service quality and consumer satisfaction on the interest in repurchasing products from the Zahra Wholesale Store. This research was conducted using quantitative methods with descriptive and verification approaches. Where data collection is done by using questionnaires and literature study.